Upaya Pencegahan Rabies di Desa Taman, Bali - Pande Ayu Naya Kasih Permatananda; Putu Nita Cahyawati; Anak Agung Sri Agung Aryastuti; Asri Lestarini (Yayasan Literasi Sains Indonesia, 2022)
Rabies is a zoonotic disease that is most feared by tourists visiting Bali because of the high mortality rate. Bali is an area with the highest Rabies incidence in Indonesia. We conducted community service in Taman Village, Bali in the form of education and implementation of mass rabies vaccination as a form of rabies prevention efforts. This community service was aimed to increase public knowledge about the danger of rabies and increase public participation in vaccinating their pets against rabies. The method of this community service consists of several stages, including dialogue and coordination with partners, preparation of facilities and infrastructure, implementation of activities and evaluation. The education provided include rabies and management of dog bite. Counseling regarding COVID-19 dan health protocols was also given on this occasion because the activities were carried out during the COVID-19 pandemic situation. This activity was attended by 20 residents as well as dog owners. The enthusiasm of the residents in the activity was very good, as evidenced by almost all the questions in the posttest that the participants were able to answer correctly. Re-exposure is given to participants who are unable to answer or answer incorrectly on the posttest. This community service is expected to be carried out regularly and continuously to eradicate rabies in Bali.